The Use of Microsoft Sway as Asynchronous Media in Improving Students’ English Learning Outcomes - Ramadhani, Rugaiyah Nur; Muliati, A.; Sofyan, Ryan Rayhana (Journal of Excellence in English Language Education, 2025)
This research aims to investigate the improvement in English learning outcomes of 11th-grade students at SMAN 5 Soppeng, using Microsoft Sway as an asynchronous medium. Involving 30 students for pre-test and post-test for quantitative data. The results showed a significant increase after treatment (Sig. = 0.000), indicating cognitive improvement in students' learning outcomes, also highlighting its potential as an effective asynchronous digital tool for fostering an effective and engaging English learning environment.